The Implementation of weekly English Conversation in Learning speaking among EFL learners - Maziyah, Faizatul; Hifdil Islam , Muhammad; Hamdani, Beny (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
Conversation is a dialog of one person to the other person to discuss something that is considered important or not. It can be done by two or more people. At this time many people use English as a means of communication with foreigners. In Indonesia, speaking English is not as easy as using Indonesian, there are differences in grammatical structure and pronunciation. Therefore, speaking English is certainly an important thing to learn and have for everyone, especially for students. This study describes the implementation of weekly conversations as a strategy in improving English speaking skills. The problem that occurs is that students are less able to improve and develop speaking skills in English in boarding schools. This study aims to 1. To describe how the English teacher applies the Weekly English Conversation in learning speaking skills 2. To find out what are the benefits of this Weekly English Conversation in speaking learning 3. To describe how students respond to the implementation of Weekly English Conversation in learning speaking. The researcher has decided to use descriptive qualitative method in investigating the problems that occur at Ulil Albab Islamic boarding school especially in the implementation of conversation. The descriptive data analysis in this research is use the process of data collection, data reduction, data display, and data verification. After conducting the research, the researcher concluded that the implementation of Weekly English Conversation can improve the English speaking skills for Students.